Pengaruh Kualitas Pelayanan, Dan Persepsi Harga Terhadap Loyalitas Konsumen(Survey Pada Rumah Makan Spesial Sambal Solo) - Mahartika, Rosiq, Dr. Anton Agus S, SE., M. Si (2016)
This study provides an overview of the phenomena that occur in a study that examines the impact of service quality and price perception on consumer loyalty Solo Special Sambal. Respondents were taken in this study as many as 97 people. The test results using multiple linear regression analysis, validity and reliability. The findings obtained in this analysis is the quality of service has a significant influence on customer loyalty with significant value 0.000 <0.05 and price perception have significant influence on customer loyalty with value signfikansi 0.004 <0.05. Determinant coefficient indicates that the variable quality of service and price perception is able to explain the loyalty of 31.5 and the remaining 68.5% there are other variables that influence it.